Pengaruh Motivasi Terhadap Kepuasan Kerja Karyawan Perbankan Di Jakarta - Anggaputra Perdana Halimun; Doniberatus Imantoro; F. Ken Wulandari; Herry Gunawan Sibarani; Siti Agustina (Universitas Prasetiya Mulya, 2018)
Banking is one of the most desirable destinations of job seekers in Jakarta, as well as being listed as the company with the highest employee turnover rate. This is interesting and become the main reason to do research in it. This study tries to explore how motivation can influence employee job satisfaction by determining motivation variables consisting of rewards, leadership style, work environment, and career development in banking industry in Jakarta, Indonesia. This study utilized quantitative survey method with total respondents of 188 people working at banks in Jakarta. The analysis technique used in this research is multiple linear regression using SPSS version 23.